Analisis Pembobotan T2 Turbo Spin Echo (TSE) brain MRI Potongan Axial dengan Penggunaan Sensitivity Encoding (SENSE) dan Tanpa Penggunaan Sense : Evaluasi pada Signal to Noise Ratio (SNR) dan Scan Time - Fani Susanto; A. Gunawan Santoso; Bagus Abimanyu (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: On examination brain MRI often finds non-cooperative patients, requiring rapid acquisition techniques. The parallel imaging sensitivity encoding (SENSE) technique utilizes spatial RF coated phased array information to reduce acquisition time by reducing the K space sampling line to produce good quality and spatial resolution, but has a limitation of signal-to-noise ratio (SNR) reduction. SENSE is used with MRI sequence pulses one of them turbo spin echo (TSE). The purpose of this study was to determine the difference of SNR and scan time on TSE T2 weighting brain MRI axial slices between use SENSE and without SENSE.Methods: This research is quantitative study with experimental approach. The data were collected from May to June 2016 at the Radiology Installation of Premier Bintaro Hospital by calculating the SNR through the software for the region of interest (ROI) and calculating the scan time through the scan timer on the workstation monitor. Data analysis was done by statistical test with SPPS 16 application using paired T-test and descriptiveResults: From the result of statistical test, it is known that SNR at TSE T2 weighting between with and without SENSE is obtained p-value 0,000 (p 0, 05). This is because the encoding of the both image are different, On TSE T2 weighting image without SENSE there is the use 1800 pulses approaching the effective TE so the shallow gradient produces maximum echo, while on TSE T2 weighting with SENSE there is a reduction of phase encoding row in K space and the presence of g-factor causes the SNR to decrease. From descriptive analysis result, is known that scan time on TSE T2 weighting between with and without SENSE usage is obtained by reduction of scan time for 1 minute 24 seconds (49, 01%). This is because the acquisition technique between the both image are different, on the TSE T2 weighting  without SENSE there is ETL in charging K space, whereas on the TSE T2 Weighting  with  SENSE there is R-factor causing the sampling not to fill all K space so that scanning time is reduced.Conclusion: There are SNR and scan time differences on TSE T2 weighting brain MRI of the axial slices with SENSE and without SENSE usage.